2022
DOI: 10.1186/s12890-022-02051-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of CXCR family members in lung adenocarcinoma with prognostic values

Abstract: Background The expression profiles and molecular mechanisms of CXC chemokine receptors (CXCRs) in Lung adenocarcinoma (LUAD) have been extensively explored. However, the comprehensive prognostic values of CXCR members in LUAD have not yet been clearly identified. Methods Multiple available datasets, including Oncomine datasets, the cancer genome atlas (TCGA), HPA platform, GeneMANIA platform, DAVID platform and the tumor immune estimation resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the yellowish pink background represents the modules that we show in detail, and the number represents the sequence of the functions. The result obtained prove that the biological functions associated with the B cell and CXCR family play significant roles in LUAD ( Gangadhar et al, 2010 ; Wang et al, 2019 ; Liao et al, 2021 ; Hu et al, 2022 ). Therefore, among the core biological functions we obtained, the biological functions of B-cell differentiation, B-cell activation, B-cell receptor signaling pathway, and CXCR chemokine receptor binding are associated with LUAD.…”
Section: Resultsmentioning
confidence: 52%
“…Furthermore, the yellowish pink background represents the modules that we show in detail, and the number represents the sequence of the functions. The result obtained prove that the biological functions associated with the B cell and CXCR family play significant roles in LUAD ( Gangadhar et al, 2010 ; Wang et al, 2019 ; Liao et al, 2021 ; Hu et al, 2022 ). Therefore, among the core biological functions we obtained, the biological functions of B-cell differentiation, B-cell activation, B-cell receptor signaling pathway, and CXCR chemokine receptor binding are associated with LUAD.…”
Section: Resultsmentioning
confidence: 52%
“…All of these genes are related to survival in patients with lung adenocarcinoma. CXC chemokine receptors play a significant role in immune surveillance, inflammation, tissue fostering and maintenance 19 . A remarkable increase in the survival rate of patients with lung adenocarcinoma was observed due to a notable increase in CXCR4 expression 19 .…”
Section: Discussionmentioning
confidence: 99%
“…CXC chemokine receptors play a significant role in immune surveillance, inflammation, tissue fostering and maintenance 19 . A remarkable increase in the survival rate of patients with lung adenocarcinoma was observed due to a notable increase in CXCR4 expression 19 . In the protein interaction network, PTPRC was most likely the core gene of the network.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed that pneumonia occurrence involved the regulation of miRNAs 13,14 . Chemokines are small molecules that can affect cancer cell proliferation and metastasis and participate in cellular secretion and structure 15 . Among them, CXC chemokines are localised on the cell membrane and are commonly expressed on the neutrophil surface.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Chemokines are small molecules that can affect cancer cell proliferation and metastasis and participate in cellular secretion and structure. 15 Among them, CXC chemokines are localised on the cell membrane and are commonly expressed on the neutrophil surface. The chemokine receptor CXCR1 is also expressed in lung structural cells, including fibroblasts.…”
Section: Introductionmentioning
confidence: 99%